An Immunohistochemical Study on the Expression of Sex Steroid Receptors in Canine Mammary Tumors. (14th February 2012) - Port Louis, Leena Rajathy; Varshney, Khub Chandra; Nair, Madhavan Gopalakrishnan
Abstract : Steroid hormones are found to play a major role in the genesis and progression of mammary tumors. The aim of this study was to immunohistochemically detect the presence of estrogen receptor alpha (ER α ), estrogen receptor beta (ER β ), and progesterone receptor (PR) and also to study the association between these markers in 29 cases of benign (11) and malignant (18) canine mammary tumors. ER α immunostaining was noticed in only one case of carcinosarcoma specifically in the nuclei of epithelial and a few myoepithelial cells. ER β immunostaining was noticed in the nuclei and cytoplasm of epithelial cells and smooth muscles lining the blood vessels. Immunoexpression of ER β was 82% in benign tumors and 78% in malignant tumors. PR immunostaining was expressed in the nuclei of epithelial cells in both benign and malignant tumors. Among the 15 PR+ cases, 6 (55%) were of benign type, and 9 (50%) were of malignant type. The most common group of hormone receptor was the ER α −/PR+/ER β + (46%) in benign tumors and ER α −/PR−/ER β + (38%) in malignant tumors. Although there was no significant association between ER α and PR with ER β, the findings indicated that ER β was consistently expressed in both benign and malignant tumors, irrespective of ER α and PR status.